Balancing Issues and Overlapping Jurisdictions in the Global Electronic Marketplace: The UCITA Example - Catherine L. Mann (Washington University Journal of Law & Policy, 2002)
The Internet marketplace is global, technologically dynamic, information-rich, and network based. Policymaking tends to be nation bound, rules oriented, and issue dependent. One example of the tension that results between the economic environment and the policymaking venue is the interdependence between tax policy and international trade negotiations. Another is the changing balance between creator and user and between individual and society in rights to intellectual property and protection of personal information. How policymakers weight these issues against the backdrop of overlapping jurisdictions will materially affect whether individuals, firms, countries, and the world as a whole will benefit from the wealth of information and the possibilities of network externalities offered by the global Internet marketplace. UCITA offers one specific lens through which to trace the tensions created by a more global, digital, and information-based marketplace.
Keywords: Electronic commerce; Uniform Computer Information Transactions Act; European Union; International; United States